In vitro production of alkaloids: Factors, approaches, challenges and prospects - Ahmad, Sayeed; Garg, Madhukar; Tamboli, Ennus Tajuddin; Abdin, M. Z.; Ansari, S. H. (Pharmacognosy Reviews, 2013)
The wide diversity of plant secondary metabolites is largely used for the production of various pharmaceutical compounds. In vitro cell tissue or organ culture has been employed as a possible alternative to produce such industrial compounds. Tissue culture techniques provide continuous, reliable, and renewable source of valuable plant pharmaceuticals and might be used for the large‑scale culture of the plant cells from which these secondary metabolites can be extracted. Alkaloids are one of the most important secondary metabolites known to play a vital role in various pharmaceutical applications leading to an increased commercial importance in recent years. The tissue culture techniques may be utilized to improve their production of alkaloids via somaclonal variations and genetic transformations. The focus of this review is toward the application of different tissue culture methods/techniques employed for the in vitro production of alkaloids with a systematic approach to improve their production.
Keywords: Alkaloids; in vitro cultures; plant tissue culture; secondary metabolites